Civil Service pay dispute, 1979 (London, 1979)
1979 1974-79 "Civil Service pay dispute, 1979" [BW0093], 1979, Trades Union Congress In July 1978, the Labour Government introduced a new guideline for pay rises of 5%. The TUC voted on 26 July to reject the limit and insist on a return to free collective bargaining. Although the government did not make the 5% limit a legal requirement, it decided to impose sanctions on government contractors who broke the limit.